Polystyrene micro and nano-particles induce metabolic rewiring in normal human colon cells: A risk factor for human health. (September 2022) - Bonanomi, Marcella; Salmistraro, Noemi; Porro, Danilo; Pinsino, Annalisa; Colangelo, Anna Maria; Gaglio, Daniela
Abstract: Polystyrene is a thermoplastic polymer widely used in commercial products. Like all plastics, polystyrene can be degraded into microplastic and nanoplastic particles and ingested via food chain contamination. Although the ecological impact due to plastic contamination is well known, there are no studies indicating a carcinogenic potential of polystyrene microplastics (MPs) and nanoplastics (NPs). Here, we evaluated the effects of the MPs and NPs on normal human intestinal CCD-18Co cells. Our results show that internalization of NPs and MPs induces metabolic changes under both acute and chronic exposure by inducing oxidative stress, increasing glycolysis via lactate to sustain energy metabolism and glutamine metabolism to sustain anabolic processes. We also show that this decoupling of nutrients mirrors the effect of the potent carcinogenic agent azoxymethane and HCT15 colon cancer cells, carrying out the typical strategy of cancer cells to optimize nutrients utilization and allowing metabolic adaptation to environmental stress conditions. Taken together our data provide new evidence that chronic NPs and MPs exposure could act as cancer risk factor for human health. Graphical abstract: Image 1 Highlights: Acute and chronic NPs and MPs exposure cause metabolic rewiring and oxidative stress. Chronic NPs or MPs exposure induces decoupling of glucose and glutamine. NPs and MPs exposure acts as a cancer risk factor for human health.